Bungo stray dogs. 03 - Asagiri, Kafka (Bungo stray dogs Dazai, Chuuya, age fifteen, 2025)
"Dazai and Chuuya have finally pegged the culprit behind this case, but what was the villain's motive? From the truth about Arahabaki to the mystery of the old boss's resurrection--all the secrets are laid bare at last! However, while they may have located their target, defeating this enemy is no easy task. Can the two boys who will one day be known as Twin Dark come together to take down a more powerful foe?!"